Investigating Potential of Wind Energy in Mahshahr, Iran. Issue 4 (August 2015) - Asakereh, Abbas; Omid, Mahmoud; Alimardani, Reza; Sarmadian, Fereydoon
In this paper, measured time-series wind speed data in two sites in Mahshahr (Iran) were analyzed to find wind energy potential of this region. The objective was to evaluate the most important characteristics of wind energy in the studied sites using means of meteorological and Weibull distribution functions. The statistical approach was used to estimate mean wind speed, wind speed distribution function, mean wind power density and mean wind energy density of the sites at heights of 10 and 40 m. Annual mean wind speeds at heights of 10 and 40 m above the ground were 4.11 and 6.08 m/s, respectively. The results revealed wide variation in the values of monthly power and energy densities in the region. The lowest and highest values of mean wind energy densities at height of 10 m were 30.8 and 111.8 kWh/m 2 /month in July and January, respectively. The winds had mean energy density of 1210 kWh/m 2 /year at 40 m height. It can be concluded that Mahshahr region has a relatively good potential for harnessing winds.